2018
DOI: 10.1002/ange.201803043
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Sugars into Chiral Polyols over a Heterogeneous Catalyst

Abstract: Transformation of sugars,w hile maintaining the intrinsic stereochemical structure,i sd esirable.H owever,s uch at ransformation requires multistep synthesis with protection and deprotection of the OH groups.Herein, anew method for selective transformation of sugar derivatives into chiral building blocks and ad iol synthon, with retention of the intrinsic configuration (stereo-and regioselectively), is demonstrated. The method is based on the selective recognition of cis-vicinal OH groups in sugars and leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…[23] More recently,T omishige and co-workers reported the synthesis of enantiopure 125PTO by two-step reduction of methyl b-l-arabinopyranoside. [24] Several recent reports have described the synthesis of 125PTO from the furfural platfom (Scheme 2). To mishige and co-workers also reported 19 %y ield of 125PTO as as ide product from An ew scalable synthesis of pentane-1,2,5-triol from the furanics platform has been developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] More recently,T omishige and co-workers reported the synthesis of enantiopure 125PTO by two-step reduction of methyl b-l-arabinopyranoside. [24] Several recent reports have described the synthesis of 125PTO from the furfural platfom (Scheme 2). To mishige and co-workers also reported 19 %y ield of 125PTO as as ide product from An ew scalable synthesis of pentane-1,2,5-triol from the furanics platform has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we used an 80:20 v/v EtOAc/EtOH solventm ixture and were glad to observe significant improvement, affording up to 63 %y ield from 1 (Table 2, entries 20-22) and up to 75 %f rom 2 (Table 2, entries[23][24][25][26]. Furthermore, we observed that in EtOAc/EtOH (80:20 v/v) the temperature had significant effect only on the hydrogenation of 1 (Table 2, entry 20 vs. 21), whereas the hydrogenation of 2 led to similaro utcomes under variousconditions (Table 2, entries[23][24][25][26][27]. 5% Ru/C catalystexhibited superior performance to Pt catalysts and provided up to 98 %y ield directly from 1 at 50 8Ci nE tOH, thus avoiding the use of more complex solventm ixtures (Table 2, entries 28 and 29).…”
mentioning
confidence: 99%